How Does Financial Expertise Moderate the Influence of Local CEOs on Tax Avoidance? - Rodhiyah Rodhiyah; Heru Tjahjono; Aminatuzzuhro Aminatuzzuhro (Pusat P2M Politeknik Negeri Batam, 2024)
This research investigates the impact of local CEOs on tax avoidance, considering how CEO financial expertise moderates this influence. Utilizing data from 665 observations of non-financial firms listed on the Indonesia Stock Exchange between 2018 and 2021, the study employs moderated regression analysis (MRA) to assess its hypotheses. Consistent with the upper echelons theory, the findings suggest that local CEOs exert a positive and significant effect on tax avoidance. Conversely, the presence of financial expertise among CEOs appears to mitigate the negative impact of local CEOs on tax avoidance. The Coarsened Exact Matching (CEM) method robustly validates these conclusions. In essence, this study underscores the significance of both CEO locality and financial expertise in shaping corporate tax avoidance behaviour.